Examining Institutional Content of the Balanced Scorecard: Logics and Translations in Ukrainian Business Environment - Firsova, Svitlana (Organizations and Markets in Emerging Economies, 2017)
This study examines institutional definitions and meanings Ukrainian managers attach to one of the most popular management concepts – the Balanced Scorecard. Socially constructed discourses, that is, beliefs, understandings, expectations, interpretations, collective cognitions and meanings beyond initial technical purposes of the BSC are treated as an institutional content that infuses and distorts technical aspects of the practice. Results confirm that technical foundations of this practice have been infused with institutionally constructed meanings and understandings generated from the local dominant institutional order, constructing the meaning of the BSC as a coercive, command-and control management system. Gathering information from local sources of information and strengthening them with collective understandings, the BSC has been infused with new meanings and beliefs, dramatically changing the original technical core of the concept. The study shows how the meaning of the management concept changed in the new institutional context under the dominance of the local logic. Specifically, the study contributes to the individual-level research on the impact of institutional logics on actors’ actions by showing the process of individuals’ responses to two macro-level meaning systems materialized in the BSC – prototypical and home institutional logics.